Total Infragastric Omentectomy Including the Vascular Perigastric Arcade in Patients With Advanced Serous Ovarian Tumors. Issue 2 (February 2017) - Cordeiro Vidal, Gloria; Croce, Sabrina; Guyon, Frédéric; Babin, Guillaume; Querleu, Denis
Abstract : Objective: The aim of this study was to document the need of including the perigastric area when performing omentectomy in patients with stage III to IV serous epithelial ovarian tumors. Patients and Methods: Patients undergoing omentectomy in the setting of surgery for advanced epithelial serous ovarian cancer between February and September 2015 were included. Patients with macroscopic involvement of the perigastric area, nonepithelial serous tumors, and recurrences of ovarian cancer were excluded. The perigastric area was isolated and comprehensively processed for pathological examination. Results: Twenty-four patients were included. Six patients underwent primary debulking surgery, and 18 patients underwent an interval debulking surgery. The mean number of pathologic blocks in the perigastric area was 24 (range, 8–41). Microscopic involvement of the perigastric omentum area was found in 62.5% of the cases. One patient had a low-grade serous carcinoma, with microscopic involvement of the perigastric area. Among the 23 patients with a high-grade serous carcinoma, 10 (83%) of 12 patients with a gross involvement of the rest of the omentum had a microscopic involvement of the perigastric area. The presence of microscopic disease in the perigastric arcade was found in 4 (36.3%) of 11 patients with a macroscopically normal omentum. Conclusions: In this study, evidence is given that total omentectomy including the perigastric area is a necessary component of complete cytoreductive surgery in advanced ovarian cancer, whatever the macroscopic appearance of the omentum.